Plant RNA Regulatory Network and RNA Granules in Virus Infection - Mäkinen, Kristiina; Lõhmus, Andres; Pollari, Maija (Frontiers in Plant Science, 2017)
Regulation of post-transcriptional gene expression on mRNA level in eukaryotic cells includes translocation, translation, translational repression, storage, nonsense-mediated decay, RNA silencing and degradation. These processes are associated with various RNA-binding proteins and cytoplasmic ribonucleoprotein (RNP) complexes many of which are conserved across eukaryotes. Microscopically visible aggregations formed by RNP complexes are termed RNA granules. Stress granules where the translationally inactive mRNAs are stored and processing bodies where mRNA decay occurs present the most studied RNA granule types. Diverse RNP-granules are increasingly being recognized to have important roles in viral infections. Although the majority of the molecular level studies on the role of RNA granules in viral translation and replication have been conducted in mammalian systems, some studies link also plant virus infection to RNA granules. An increasing body of evidence indicates that plant viruses require components of stress granules and processing bodies for their replication and translation, but how extensively the cellular mRNA regulatory network is utilized by plant viruses has remained largely enigmatic. Antiviral RNA silencing, which is an important regulator of viral RNA stability and expression in plants, is commonly counteracted by viral suppressors of RNA silencing. Some of the RNA silencing suppressors have been localized to cellular RNA granules and proposed to carry out their suppression functions there. Plant NB-LRR protein-mediated virus resistance has been linked to enhanced processing body formation and translational repression of viral RNA. Many interesting questions relate to how the pathways of antiviral RNA silencing leading to viral RNA degradation and/or repression of translation, suppression of RNA silencing and viral RNA translation converge in plants and how different RNA granules and their individual components contribute to these processes. In this review we discuss the roles of cellular RNA regulatory mechanisms and RNA granules in plant virus infection in the light of current knowledge and compare the findings with those made on animal virus studies.